Seebeck Tensor Analysis of (p × n)-type Transverse Thermoelectric Materials. (11th March 2019) - Shao, Qing; Kanakkithodi, Arun Mannodi; Xia, Yi; Chan, Maria K.Y.; Grayson, Matthew
ABSTRACT: Single-leg (p × n)-type transverse thermoelectrics (TTE) are reviewed as an alternative to conventional or "longitudinal" double-leg thermoelectrics for applications at room temperature and below. As the name suggests, this unique behavior of (p × n)-type transverse thermoelectrics results from choosing ambipolar anisotropic materials that have a Seebeck tensor with orthogonal p- and n-type Seebeck coefficients, leading to transverse relation between net heat and net electrical current. One feature of such materials is that they can operate near intrinsic doping and, therefore will not suffer from dopant freeze-out, opening the possibility of new cryogenic operation for solid state cooling. In this work, a Seebeck tensor analysis of thermoelectric materials is presented. To compare the performance of transverse thermoelectric materials, a transverse power factor PF⊥ is introduced. Materials searches based on these simple criteria reveal that over 1/4 of the database of about 48, 000 inorganic materials could potentially function as (p × n)-type TTE's, demonstrating the underappreciated prevalence of this class of materials.